Introducing anthropology what makes us human? - Pountney, Laura; Maric, Tomislav (Cambridge, United Kingdom Polity Press, 2021)
"Introduces the fascinating study of the planet's most captivating species"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Anthropology; Human evolution; Human beings -- Origin